Effects of Resistance Exercise on Muscle Mass, Strength, and Physical Performances in Elderly with Diagnosed Sarcopenia: A Systematic Review and Meta-Analysis - Kyung Min Kim; Hyun Joo Kang (운동과학, 2020)
PURPOSE Sarcopenia, also known as the age-related loss of muscle mass and muscle fitness, and physical performance, has been related to many adverse health outcomes. Resistance exercise may have an important role in effecting strategy for sarcopenia in aging populations. The purpose of this study is to systematically assess the effects resistance exercise interventions on muscle mass, muscle strength, and physical performance in elderly diagnosed with sarcopenia. METHODS A comprehensive search on electronic databases, including PubMed, EMBASE, CINAHLPlus, SPORTDiscus, KERIS, KISS, and NAL were conducted. Eligible studies were divided into exercise and randomized controlled trials in elderly with sarcopenia. Searches retrieved 1,067 titles. Eighty full texts were evaluated, and seven studies were used for final systematic reviews. CMA (Comprehensive Meta-Analysis) ver 3.0 was used for meta-analysis. RESULTS Meta-analysis showed that lower muscle mass (ES=0.579, 95% CI: 0.266-0.892, p=.000), appendicular muscle mass (ES=0.341, 95% CI: 0.006-0.676, p=.046), right hand grip strength (ES=0.739, 95% CI: 0.216-1.262, p=.006), left hand grip strength (ES=0.692, 95% CI: 0.167-1.217, p=.010), knee extension strength (ES=1.448, 95% CI: 0.273-2.624, p=.016), and timed up and go (ES=1.471, 95% CI: 0.492-2.450, p=.003) significantly improved in response to resistance exercise programs. CONCLUSIONS Sarcopenia is increasing with the growing elderly population; thus prevention and effective interventions are very important. The data suggest that resistance exercise may be actual in enhancing not only appendicular muscle mass, but also knee extension strength and timed up and go in elderly diagnosed with sarcopenia. Further follow-up studies on larger populations and a variety of approaches are required to reconfirm these results.